2000
DOI: 10.1046/j.1432-1327.2000.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionarily conserved porcupine gene family is involved in the processing of the Wnt family

Abstract: The Drosophila segment polarity gene product Porcupine (Porc) was first identified as being necessary for processing Wingless (Wg), a Drosophila Wnt (Wnt) family member. Mouse and Xenopus homologs of porc (Mporc and Xporc) were identified and found to encode endoplasmic reticulum (ER) proteins with multiple transmembrane domains. In contrast with porc, four different types of Mporc and Xporc mRNA (A±D) are generated from a single gene by alternative splicing. Mporc mRNA is differentially expressed during embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 14 publications
2
67
0
Order By: Relevance
“…Numerous studies have shown that the segment polarity gene porcupine (porc) is required for the maintenance of Wg signaling in this tissue. Genetic epistasis analyses demonstrated that porcupine acts upstream of intracellular signaling components in a cell non-autonomous manner (van den Heuvel et al, 1993;Noordermeer et al, 1994;Siegfried et al, 1994;Manoukian et al, 1995;Tanaka et al, 2000). In addition, a genetic screen for maternally expressed genes required for the endoderm induction in Caenorhabditis elegans confirmed the cell non-autonomous role of mom-1 (C. elegans porcupine ortholog) in Wnt signaling (Thorpe et al, 1997).…”
Section: Porcupine Lipid Modifies Wntsmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies have shown that the segment polarity gene porcupine (porc) is required for the maintenance of Wg signaling in this tissue. Genetic epistasis analyses demonstrated that porcupine acts upstream of intracellular signaling components in a cell non-autonomous manner (van den Heuvel et al, 1993;Noordermeer et al, 1994;Siegfried et al, 1994;Manoukian et al, 1995;Tanaka et al, 2000). In addition, a genetic screen for maternally expressed genes required for the endoderm induction in Caenorhabditis elegans confirmed the cell non-autonomous role of mom-1 (C. elegans porcupine ortholog) in Wnt signaling (Thorpe et al, 1997).…”
Section: Porcupine Lipid Modifies Wntsmentioning
confidence: 98%
“…In Drosophila, porcupine-mutant cells accumulate Wg protein suggesting that the protein in unable to be released from the producing cells (van den Heuvel et al, 1993;Noordermeer et al, 1994;Siegfried et al, 1994;Tanaka et al, 2000). In porcupine-mutant flies, a much smaller fraction of Wg is found associated with cell membranes as compared to wild-type animals (Zhai et al, 2004).…”
Section: Porcupine Lipid Modifies Wntsmentioning
confidence: 99%
“…Despite the multitude of cellular responses that they elicit, all 19 secreted Wnt family members are dependent upon the same biosynthetic enzymes, including Porcupine (Porcn), a multipass acyltransferase localized to the endoplasmic reticulum (ER) that supplies a single fatty acid adduct necessary for Wnt protein exit from the secretory pathway (3)(4)(5)(6). Transport of Wnt protein to the cell surface from the ER requires interaction of the putative lipoprotein receptor Wntless, a seven-transmembrane protein that facilitates acylated Wnt protein secretion (7).…”
mentioning
confidence: 99%
“…Briefly, the WNT proteins that are synthesized with the endoplasmic reticulum (ER), are known to be palmitoyleated via the Porcupine (PORCN) to form the WNT ligand, which is then ready for transportation 15 . It is believed that these ligands are then transported via the EVI/WNTLESS transmembrane complex out of the cell 16 & 17 .…”
Section: Introductionmentioning
confidence: 99%